Revolutionizing Drug Delivery: The Promise of Self-emulsifying Systems in Overcoming Bioavailability Challenges - Dhiman, Sonia; Mannan, Ashi; Mohan, Maneesh; Singh, Thakur Gurjeet (Current Drug Research Reviews, 2025)
<span class=
Keywords: dosage form